2015
DOI: 10.1530/rep-14-0613
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of the sex chromosomes during spermatogenesis

Abstract: Mammalian sex chromosomes arose from an ordinary pair of autosomes. Over hundreds of millions of years, they have evolved into highly divergent X and Y chromosomes and have become increasingly specialized for male reproduction. Both sex chromosomes have acquired and amplified testis-specific genes, suggestive of roles in spermatogenesis. To understand how the sex chromosome genes participate in the regulation of spermatogenesis, we review genes, including single-copy, multi-copy, and ampliconic genes, whose sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 129 publications
(193 reference statements)
0
9
0
Order By: Relevance
“…Several studies have concluded that the X chromosome is still under the influence of MSCI after meiosis since they observed that only a small number of genes are expressed from the X chromosome in post-meiotic cells [25, 50, 51]. These studies were based on microarray analyses and either ignored multicopy genes or considered all genes of the same family (all copies of the same gene) as one gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have concluded that the X chromosome is still under the influence of MSCI after meiosis since they observed that only a small number of genes are expressed from the X chromosome in post-meiotic cells [25, 50, 51]. These studies were based on microarray analyses and either ignored multicopy genes or considered all genes of the same family (all copies of the same gene) as one gene.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this finding was also proven to be imprecise by other contemporaries (Curtsinger et al, 1983;Martin et al, 1995a,b). Apart from the debate, it has been reported that an active gene transcription occurs selectively in the chromosomes (including sex chromosomes) of haploid round spermatids (Hu and Namekawa, 2015). Therefore, if the composition of sex chromosomes has changed due to the post-meiotic modifications in the gene expression and differential survival of spermatozoa during epididymal maturation, these may affect the expected ratio (Bean, 1990).…”
Section: Ratiomentioning
confidence: 99%
“…During spermatogenesis, the sex chromosomes are tightly regulated through the generally repressive epigenetic environments of MSCI and PSCR (Turner 2007;Hu and Namekawa 2015). For example, PSCR in mice is partially maintained by the multicopy Y-linked Sly gene (Cocquet et al 2009(Cocquet et al , 2010.…”
Section: Regulatory Evolution and Spermatogenesismentioning
confidence: 99%